BOARD SIZE AND CORPORATE PERFORMANCE OF QUOTED COMMERCIAL BANKS IN NIGERIA - Martins, Otuedon Ajuyitse; Osemudiamen, Ogbole Philip (International Journal of Research -GRANTHAALAYAH, 2019)
The study examines board size and corporate performance of quoted companies in Nigeria. The objectives of the study are to examine the relationship between board size and total asset of quoted Nigerian banks; to examine the relationship between board size and total revenue of quoted Nigerian banks; to examine the relationship between board size and net profit of quoted Nigerian banks. The study adopted panel research design and census survey approach. The population of this research consists of 21 commercial banks in Nigeria. Data were collected from secondary sources that is audited financial statements. The findings of the study showed that there is a negative relationship between board size and total assets; there is a positive relationship between board size and gross revenue; there is a positive relationship between board size and Net profit. From the above findings, the study concluded that there is a relationship exist between board size and corporate performance of quoted Nigerian banks. The study further recommend that commercial banks and quoted firms must ensure that a proper board of directors is composed in other to institute standards and controls that will boost the net income of the firm; regulatory bodies should ensure that firms constitute a board with a standard size of seven members. The board also must have professionals who have requisite knowledge in the business; firm’s board must ensure that the committees in the board are most effective in safeguarding the asset of the organization and should continuously make decisions that will boost the revenue and net profit of the firm.